Attitude, job motivation, job satisfaction and behavioural intention among tour guides in Sarawak / Khairul Hisham Ismail...[et al.] - Ismail, Khairul Hisham; Sarkawi, Redzuan; Ismail, Hasbullah (2016)
This study is about attitude,job motivation, job satisfaction and behavioural intention among tour guides in Sarawak. Job motivation is affected by extrinsic factors and instrinsic factors. Extrinsic factors are company policy and administration, relationship with colleagues, salary, security, status, supervision, and work condition, while intrinsic factors are achievement, advancement, promotional oppurtunities, autonomy, freedom, growth, recognition, responsibility, and work itself. A total of 74 tour guides took part in this survey which utilized purpossive data sampling technique. The data was collected using self-administered questionnaires. Findings showed that the tour guides have positive attitude towards their job, are mostly motivated by the intrinsic factors and are generally satisfied with their job. This findings suggested that there is a strong and positive relationship between attitude and job motivation, a strong relationship between job satisfaction and job motivation. However, there is a positive but weak relationship between behavioural intention and attitude, intrinsic factor, extrinsic factors, job motivation and job satisfaction.